EZ Lock / Muhammad Hafeez Hashim - Hashim, Muhammad Hafeez (2020)
At this stage, a detail study about EZ lock for my new product development was done. It is necessary in order to get detailed information about the product, non-verbal interview and research on the innovation product based and its features, quality, and conveniences. Furthermore, the theory of the new product development was related to my product concept. The details of my product were divided into research and development, product design, features, concept testing, build prototype and test marketing. In research and development, the details explanation of how the idea generation and market survey was conducted. The idea actually was generated based on the problem for the bikers and students in using their present bike lock which are not convenient and not enough secured. It is also waste time in finding the bike lock’s key and sometimes student often forgot where the last time they put their key. Next, the details study based on target market for my product is bike store and hardware store which is the attractive sport for the people that looking for the bike lock. From the idea generation and market survey done, it shows the summary of the product detail, analysis and also target market on how our product idea was develop. The things that was analyzed is the product design or features. At this part, a sketch of my product design was done based on combination of existing product in market. Concept testing is the further analysis of the product on how target market will accept the innovation product.